Role of Relaxation in Pregnancy Health in Quran - Nikzad Iesazadeh; Reza Salimi (Tehran University of Medical Sciences, 2014)
Background & Aim: One of the key factors affecting the physical and mental health of fetus is peace. According to Quran, this factor is a fundamental Principle in different fields of Islamic Ethics and law and it also affects all orders and Prohibitions. That's because of conditions that are ordained during Pregnancy Period and of course it affects the benefits and losses of the Person in next Periods of growth. This study assessed the fundamental role of peace during pregnancy and fetal life from the perspective of the holy Quran and its priority to other functions of marriage .   Methods & Materials: This study is a retrospective review which was performed by searching library sources and 15 relevant sources were found. The concept of peace in holy Quran can be followed by keywords such as, Assurance / Etminan (Raad/28), tranquility/ Sakineh ( Fath/24), inhabitancy / Sakana (Tobeh/103), Security / Amniyat (Thein/3), Permanency / Sobat( Forghan/47). In addition, Keywords such as, Health, Pregnancy, and Sprit were studied too .   Results: Meanwhile, the topic of marriage and finding a family (including matrimony, spousal time, pregnancy and reproduction) is a composition of religious orders and prohibitions. According to some studies based on the Quran's verses and his successor's anecdote considerable results such as reproduction, correct sexual satisfactory, moral and psychological peace was achieved. Relaxation in pregnancy phase is very important and vital process for the embryonic formation particularly in view of his/her future corporeal and spiritual life. Such standpoint is firmly emphasized by Islamic orders due to healthy generation among the human being .   Conclusion: Aquiring spiritual relaxation and developing it according to psychological guidelines and strategies of the holy Quran is necessary to achieve a peaceful and satisfactory condition during pregnancy and birth of a healthy and righteous child .